Proceedings of the UNC CBE Summit 2017 - Solér, Michelle (The University of North Carolina Press, 2017)
The University of North Carolina CBE Summit 2017 offered faculty and staff from around the country an opportunity to learn about competency-based education (CBE) models. CBE enables students to earn academic credit based on content proficiency rather than the amount of time spent enrolled in a course. For the 300 participants at the Summit, the sessions focused on broad challenges to implementing CBE into established higher education systems. Nearly sixty national experts covered a broad range of topics as they engaged with teams from UNC's seventeen campuses, the University System of Georgia, and representatives from community colleges and other higher education institutions, discussing the latest trends in competency-based instruction and delivery models. The six essays in this volume were adapted from presentations given at the 2017 Summit.